Analysis of the Potential Distribution of Eels (Anguilla spp.) Along the Luk Ulo River, Kebumen Regency, Central Jawa, Indonesia - Waluyo; Hiskia Marceliko; Ellia Debby Leonny Putri Siswantoro (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2026)
Eels are catadromous fish that utilize river systems, especially estuaries, as migration corridors from marine to upstream habitats. This study assessed the abundance potential and spatial distribution of eels in the Luk Ulo River, Kebumen Regency, to support conservation efforts. Sampling was conducted at 10 stations from upstream areas to the estuary. Analyses included morphometric identification, spatial distribution, length–weight relationships, growth modeling, Principal Component Analysis, and cross-correlation with environmental parameters. A total of 30 individuals were collected, consisting of two species: Anguilla bicolor bicolor (22 individuals) and A. marmorata (8 individuals). Most specimens (93.54%) were in the yellow eel phase, indicating a growth stage dominance, while 6.45% were elvers. The mean length was 49.90 cm (SD = 34.95 cm), with non-normal distribution (p < 0.05) and dominance in the 32–48 cm size class. Growth followed a negative allometric pattern (W = 0.00083L2.87), where length increases faster than weight, with a high determination coefficient (R² ≈ 0.93), indicating a strong relationship between length and weight. The population structure suggests that the Luk Ulo River primarily functions as a growth habitat with stable environmental conditions. Cross-correlation analysis showed strong positive relationships between eel abundance and salinity (r > 0.81), total dissolved solids (r > 0.79), and phosphate (r > 0.61), indicating that higher values of these parameters are associated with increased eel presence.